2018
DOI: 10.1007/s00705-018-3912-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of expression of BmNPV cg30 by bmo-miRNA-390 is a host response to baculovirus invasion

Abstract: Bombyx mori larvae exhibit in vivo defensive reactions immediately after invasion by a virus. One of these defense systems is to express appropriate microRNAs (miRNAs) to respond to the infection. A novel Bombyx mori-encoded miRNA, bmo-miR-390, was identified previously by high-throughput sequencing. Based on bioinformatic predictions, the Bombyx mori nuclear polyhedrosis virus cg30 gene (BmNPV-cg30) is one of the target genes of bmo-miR-390. In this study, expression vectors with an enhanced green fluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…The silkworm-encoded miRNA bmo-miR-2819 is upregulated at the delayed early stage in infection, and its overexpression inhibits BmNPV proliferation by downregulating viral ie-1 ( 66 ). Similarly, bmo-miRNA-390 downregulates the expression of BmNPV- cg30 ( 67 ). The PIWI-associated RNA (piRNA) pathway is also involved in an antiviral response but little information is reported in silkworm ( 68 ).…”
Section: Silkworm Immune Response To Baculovirusmentioning
confidence: 99%
“…The silkworm-encoded miRNA bmo-miR-2819 is upregulated at the delayed early stage in infection, and its overexpression inhibits BmNPV proliferation by downregulating viral ie-1 ( 66 ). Similarly, bmo-miRNA-390 downregulates the expression of BmNPV- cg30 ( 67 ). The PIWI-associated RNA (piRNA) pathway is also involved in an antiviral response but little information is reported in silkworm ( 68 ).…”
Section: Silkworm Immune Response To Baculovirusmentioning
confidence: 99%
“…In BmNPV-infected larvae, 38 DEmiRNAs were identified to be involved in several functions, including innate immune responses . Several viral genes, including odv-e18 , orf118 , me53 , orf98a p43, etc., were predicted to be potential targets of the B. mori miRNA, bmo-miR-390 . Bantam miRNA is crucial in anti-AcMNPV responses in S. litura and S. exigua , where the inhibition of bantam increases the viral load and upregulated viral genes. , Investigations conducted in AcMNPV-infected Sf9 cells revealed the differential expression of numerous conserved and novel miRNAs .…”
Section: Discussionmentioning
confidence: 99%
“…More and more studies had shown that miRNAs play key roles in host‐pathogen interactions by regulating the expression of host immune genes or viral genes, affecting viral replication (Chawla & Sokol, 2011; Kang et al, 2018; Mead & Tu, 2008; Padmanabhan et al, 2009; Simón‐Mateo & García, 2006). Studies have also confirmed that cellular miRNAs and viral miRNAs contribute to host immunity and host–pathogen interaction by regulating the expression of host or pathogen‐related genes in various organisms (Y. Li, Qin, et al, 2019; Ryan & Williams, 2019; Wu et al, 2013, 2016).…”
Section: Discussionmentioning
confidence: 99%